Cultural sexism the politics of feminist rage in the #metoo era - Savigny, Heather 1969- (Bristol University Press, 2020)
How does gendered power work? How does it circulate? How does it become embedded? And most importantly, how can we challenge it? Heather Savigny highlights five key traits of cultural sexism - violence, silencing, disciplining, meritocracy and masculinity - prevalent across the media, entertainment and cultural industries that keep sexist values firmly within popular consciousness. She traces the development of key feminist thinkers before demonstrating how the normalization of misogyny in popular media, culture, news and politics perpetuates patriarchal values within our everyday social and cultural landscape. She argues that we need to understand why #MeToo was necessary in the first place in order to bring about impactful, lasting and meaningful change